Copper-promoted/copper-catalyzed trifluoromethylselenolation reactions - Ghiazza, Clément; Tlili, Anis (Beilstein Journal of Organic Chemistry, 2020)
Copper catalysis and, more generally, copper chemistry are pivotal for modern organofluorine chemistry. Major advances have been made in the field of trifluoromethylselenolations of organic compounds where copper catalysis played a crucial role. Recent developments in this field are highlighted in this minireview.
Keywords: copper catalysis; fluorine; homogenous catalysis; trifluoromethylselenolation

(untitled) - Hansch, C.; Leo, A.; Taft, R. W. (Chem. Rev., 1991)

Modern Fluoroorganic Chemistry - Kirsch, P. (Wiley-VCH, 2013)

(untitled) - Leroux, F. R.; Manteau, B.; Vors, J.-P.; Pazenok, S. (Beilstein J. Org. Chem., 2008)

(untitled) - Besset, T.; Jubault, P.; Pannecoucke, X.; Poisson, T. (Org. Chem. Front., 2016)

(untitled) - Tlili, A.; Toulgoat, F.; Billard, T. (Angew. Chem., Int. Ed., 2016)

(untitled) - Xu, X.-H.; Matsuzaki, K.; Shibata, N. (Chem. Rev., 2015)

(untitled) - Barata-Vallejo, S.; Bonesi, S.; Postigo, A. (Org. Biomol. Chem., 2016)

Modern Synthesis Processes and Reactivity of Fluorinated Compounds - Toulgoat, F.; Billard, T. (Toward CF3S Group: From Trifluoromethylation of Sulfides to Direct Trifluoromethylthiolation, 2017)

Copper-Mediated Cross-Coupling Reactions - Evano, G.; Blanchard, N. (John Wiley & Sons, Inc., 2013)

(untitled) - Tlili, A.; Ismalaj, E.; Glenadel, Q.; Ghiazza, C.; Billard, T. (Chem. – Eur. J., 2018)

(untitled) - Ghiazza, C.; Billard, T.; Tlili, A. (Chem. – Eur. J., 2019)

(untitled) - Kondratenko, N. V.; Kolomeytsev, A. A.; Popov, V. I.; Yagupolskii, L. M. (Synthesis, 1985)

(untitled) - Chen, C.; Ouyang, L.; Lin, Q.; Liu, Y.; Hou, C.; Yuan, Y.; Weng, Z. (Chem. – Eur. J., 2014)

(untitled) - Rong, M.; Huang, R.; You, Y.; Weng, Z. (Tetrahedron, 2014)

(untitled) - Wu, C.; Huang, Y.; Chen, Z.; Weng, Z. (Tetrahedron Lett., 2015)

(untitled) - Tian, Q.; Weng, Z. (Chin. J. Chem., 2016)

(untitled) - Zhang, Y.; Yang, D.-Y.; Weng, Z. (Tetrahedron, 2017)

(untitled) - Wang, Y.; You, Y.; Weng, Z. (Org. Chem. Front., 2015)

(untitled) - Yang, Y.; Lin, X.; Zheng, Z.; Lin, G.; Zhang, Y.; You, Y.; Weng, Z. (J. Fluorine Chem., 2017)

(untitled) - Chen, T.; You, Y.; Weng, Z. (J. Fluorine Chem., 2018)

(untitled) - Zhu, P.; He, X.; Chen, X.; You, Y.; Yuan, Y.; Weng, Z. (Tetrahedron, 2014)

(untitled) - Hou, C.; Lin, X.; Huang, Y.; Chen, Z.; Weng, Z. (Synthesis, 2015)

(untitled) - Wang, J.; Zhang, M.; Weng, Z. (J. Fluorine Chem., 2017)

(untitled) - Zhang, M.; Weng, Z. (Org. Lett., 2019)

(untitled) - Zhang, B.-S.; Gao, L.-Y.; Zhang, Z.; Wen, Y.-H.; Liang, Y.-M. (Chem. Commun., 2018)

(untitled) - Tyrra, W.; Naumann, D.; Yagupolskii, Y. L. (J. Fluorine Chem., 2003)

(untitled) - Lefebvre, Q.; Pluta, R.; Rueping, M. (Chem. Commun., 2015)

(untitled) - Matheis, C.; Krause, T.; Bragoni, V.; Goossen, L. J. (Chem. – Eur. J., 2016)

(untitled) - Matheis, C.; Wagner, V.; Goossen, L. J. (Chem. – Eur. J., 2016)

(untitled) - Magnier, E.; Wakselman, C. (Collect. Czech. Chem. Commun., 2002)

(untitled) - Dale, J. W.; Emeléus, H. J.; Haszeldine, R. N. (J. Chem. Soc., 1958)

(untitled) - Stump, E. C. (Chem. Eng. News, 1967)

(untitled) - Glenadel, Q.; Ismalaj, E.; Billard, T. (J. Org. Chem., 2016)

(untitled) - Ghiazza, C.; Billard, T.; Tlili, A. (Chem. – Eur. J., 2017)

(untitled) - Ghiazza, C.; Tlili, A.; Billard, T. (Molecules, 2017)

(untitled) - Glenadel, Q.; Ghiazza, C.; Tlili, A.; Billard, T. (Adv. Synth. Catal., 2017)

(untitled) - Ghiazza, C.; Debrauwer, V.; Billard, T.; Tlili, A. (Chem. – Eur. J., 2018)

(untitled) - Ghiazza, C.; Billard, T.; Dickson, C.; Tlili, A.; Gampe, C. M. (ChemMedChem, 2019)

(untitled) - Chen, C.; Hou, C.; Wang, Y.; Hor, T. S. A.; Weng, Z. (Org. Lett., 2014)

(untitled) - Chen, X.-L.; Zhou, S.-H.; Lin, J.-H.; Deng, Q.-H.; Xiao, J.-C. (Chem. Commun., 2019)

(untitled) - Nikolaienko, P.; Rueping, M. (Chem. – Eur. J., 2016)